THE RIGHT TO LIFE FROM THE PERSPECTIVE OF MAQĀṢID AL-SHARĪʿAH: QUESTIONING THE LEGITIMACY OF ISLAMIC LAW IN CASES OF SUICIDE BOMBINGS - Sobirin; Masruri; Hema Malini; Abdul Wahid al-Anshori (Journal of Islamic and Interdisciplinary Research, 2026)
This article examines the right to life (ḥifẓ al-nafs) from the perspective of maqāṣid al-sharī‘ah by critically questioning the legitimacy of Islamic law claims used to justify suicide bombings. Departing from the normative and ethical foundations of Islamic law, the study argues that the protection of human life constitutes one of the most fundamental objectives (al-darūriyyāt) of the Sharī‘ah and cannot be compromised under any circumstances. Employing qualitative library research with a normative-philosophical and maqāṣid-oriented approach, this article analyzes classical and contemporary Islamic legal thought, relevant Qur’anic verses, Prophetic traditions, fatwas, and legal frameworks related to human rights. The findings demonstrate that suicide bombings fundamentally contradict the core objectives of Islamic law, particularly the preservation of life, security, and human dignity. Claims that frame such acts as forms of jihād are shown to rely on reductive and literalist interpretations that neglect the broader ethical and teleological dimensions of Sharī‘ah. This study concludes that suicide bombings represent a severe deviation from the maqāṣid al-sharī‘ah and undermine Islam’s universal commitment to justice, peace, and the protection of human life.